Development of a Hypersensitive Periodate‐Cleavable Amino Acid that is Methionine‐ and Disulfide‐Compatible and its Application in MHC Exchange Reagents for T Cell Characterisation. Issue 1 (23rd December 2012) - Amore, Alessia; Wals, Kim; Koekoek, Evelyn; Hoppes, Rieuwert; Toebes, Mireille; Schumacher, Ton N. M.; Rodenko, Boris; Ovaa, Huib
Abstract Incorporation of cleavable linkers into peptides and proteins is of particular value in the study of biological processes. Here we describe the synthesis of a cleavable linker that is hypersensitive to oxidative cleavage as the result of the periodate reactivity of a vicinal amino alcohol moiety. Two strategies directed towards the synthesis of a building block suitable for solid‐phase peptide synthesis were developed: a chemoenzymatic route, involving L‐threonine aldolase, and an enantioselective chemical route; these led to α, γ‐diamino‐β‐hydroxybutanoic acids in diastereoisomerically mixed and enantiopure forms, respectively. Incorporation of the 1, 2‐amino alcohol linker into the backbone of a peptide generated a conditional peptide that was rapidly cleaved at very low concentrations of sodium periodate. This cleavable peptide ligand was applied in the generation of MHC exchange reagents for the detection of antigen‐specific T cells in peripheral blood cells. The extremely low concentration of periodate required to trigger MHC peptide exchange allowed the co‐oxidation of methionine and disulfide residues to be avoided. Conditional MHC reagents hypersensitive to periodate can now be applied without limitations when UV irradiation is undesired or less practical.